Third‐personal evidence for perceptual confidence. - Morrison, John (Philosophy & Phenomenological Research, 2024)
Perceptual Confidence is the view that our conscious perceptual experiences assign confidence. In previous papers, I motivated it using first‐personal evidence (Morrison, 2016), and Jessie Munton motivated it using normative evidence (Munton, 2016). In this paper, I will consider the extent to which it is motivated by third‐personal evidence. I will argue that the current evidence is supportive but not decisive. I will then describe experiments that might provide stronger evidence. I hope to thereby provide a roadmap for future research.